Evaluation of stroke mortality and related risk factors: A single-center cohort study from Gaziantep, Turkey - Kocamer Şimşek, Betül; Özer, Gökhan (Journal of Surgery and Medicine, 2019)
Aim: In most cases diabetes worsens the outcome of acute stroke. Acute hyperglycemia, higher C-reactive protein (CRP) and fibrinogen levels predict increased risk of in-hospital mortality. However, pneumonia is found to be major causes of death after stroke. In this study we aimed to define the risk factors of mortality of ischemic stroke. Methods: This study was an analysis of retrospectively collected data of patients treated in intensive care unit (ICU) due to ischemic stroke. Results: One hundred twenty-eight patients’ files were evaluated. Mortality rate was 30.4% (n=39). The risk of stroke death was higher in presence of adverse events in ICU, presence of pneumonia findings, trans-tracheal intubation, long ICU stay, higher heart beats, lower SPO2 and pH levels, higher blood glucose and fibrinogen levels, higher CRP levels and the variation of CRP, higher APACHI-II, A2DS2 (risk of stroke) scores and lower GCS scores. Pneumonia was the most adverse event in ICU and the second most reason of the death. Conclusions: APACHI-II, A2DS2 scores and GCS scores can predict the stroke death, and preventing the pneumonia may decrease acute mortality rate of ischemic stroke. CRP together with fibrinogen levels can be used as a prognostic factor in ischemic stroke.